COVID-19 vaccine acceptance and related behavioral and psychological characteristics in individuals with mental disorders in Korea - Ryu, Seunghyong; Kang, Hangoeunbi; Jung, Ha-Ran; Yun, Hyunju; Kang, Shi-Hyun; Kim, Tae-Suk; Choi, Seunggi; Kim, Ju-Wan; Lee, Ju-Yeon; Kim, Jae-Min; Jung, Sook-In; Yoon, Bo-Hyun; et al. (Frontiers in Psychiatry, 2023)
Objective: This study aimed to investigate COVID-19 vaccine acceptance and related factors in individuals with mental disorders in Korea. Methods: We surveyed 572 individuals with mental disorders about their attitudes toward COVID-19 vaccination using a 7-item self-rating questionnaire on vaccine acceptance and hesitancy. We categorized the respondents into groups based on their level of vaccine acceptance using hierarchical clustering. In addition, we evaluated the respondents' vaccination status and trust in sources of information regarding COVID-19 vaccines, and assessed their psychological characteristics using the Patient Health Questionnaire-9, Gratitude Questionnaire-6, and Big Five Inventory-10. Results: Clustering revealed three groups according to vaccine acceptance: ‘totally accepting’ (n = 246, 43.0%), ‘somewhat accepting’ (n = 184, 32.2%), and ‘hesitant’ (n = 142, 24.8%) groups. Three quarters of all participants, who belonged to the ‘totally accepting’ or ‘somewhat accepting’ groups, were willing to receive a COVID-19 vaccine despite concerns about its side effects. Individuals in the high vaccine acceptance group were older (F = 12.52, p < 0.001), more likely to receive the influenza vaccine regularly, and more likely to trust formal information sources. Additionally, they had higher levels of gratitude (F = 21.00, p < 0.001) and agreeableness (F = 4.50, p = 0.011), and lower levels of depression (χ2 = 11.81, p = 0.003) and neuroticism (F = 3.71, p = 0.025). Conclusion: The present study demonstrated that individuals with mental disorders were generally willing to receive COVID-19 vaccination. However, they weighed its need and effectiveness against potential side effects before coming to a decision. It is important to understand the behavioral and psychological characteristics associated with vaccine acceptance, to effectively communicate its importance to individuals with mental disorders.